Increasing Students' Cognitive Absorption Through Remedial Learning in Physics - Asis, Asmawati; Ching, Chin Peng; Suttiwan, Witsanu (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: To determine whether there is an increase in junior high school students' absorption of physics subjects after participating in remedial learning. Methodology: This type of research is classroom action research. Junior high school students as subjects subjected to action in this study. The sampling technique in this study used purposive sampling. The instruments used in this study were diagnostic tests, final tests, observation guidelines. The collected data were analyzed using quantitative analysis. Main Findings: The application of remedial learning has been able to help students increase their cognitive absorption from one cycle to the next. Novelty/Originality of this study: The novelty of this research is that teachers can find out one of the learning methods to increase students' absorption and add insight into learning strategies.